An Assessment of Online Newspaper Readership among Residents of Apata, Ibadan, Nigeria - Ayobolu, Yetunde Oluwayemisi (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The rapid growth of digital technology has revolutionised the media landscape significantly altering the ways people access news and information. Online newspapers have emerged as a popular platform for news disseminating, offering numerous benefits over traditional print media. This study investigates online newspaper readership among the residents of Apata, Ibadan due to its demographic uniqueness and dense population. The survey method with the use of questionnaires was utilised for data collection from two hundred and fifty participants randomly selected. Results revealed that 70% access online news daily, with 60% preferring social media platforms. Factors influencing online newspaper readership include age, education, income, and internet access, indicating high reliance on online platforms for news consumption within the community. The study applies the Uses and Gratification Theory (UGT) as it explains the motivation behind the residents’ preferences for specific online platforms and Diffusion of Innovation Theory to shed light on the adoption of digital news consumption as a modern trend. Results reveal that participants primarily consume online news for informational needs, entertainment, and fostering social interaction. Based on findings, the study recommends that online newspaper publishers enhance mobile-friendly accessibility, leverage social media integration, and offer localized content to boost engagement among Apata residents. Findings from the study contribute to understanding online newspaper readership in Nigeria and inform media development in the digital age.